Implications of Progressive Islamic Jurisprudence (Risalah Islam Berkemajuan) on Muhammadiyah Legal Thought: An Ontological Review - Isman; Afief El Ashfahany; Fauzul Hanif Noor Athief; Azhar Alam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this study is to investigate the conceptual and practical implications of Progressive Islamic Jurisprudence (Risalah Islam Berkemajuan) within the legal thought school of Muhammadiyah. To bridge the difference between Muhammadiyah's legal thought and practice, the study adopts an ontological perspective. The research utilises a detailed analysis of the ontological notion of Progressive Islamic Law, examining its relationship with natural law and positivist perspectives. The study discovered that this legal ontology incorporates religious values, justice, and social change. The key contribution of the investigation is to develop principles of Progressive Islamic Law that can direct the advancement of Muhammadiyah's legal curriculum and practice. Although the research establishes a sound theoretical foundation, practical constraints in implementing the ontology may arise. The implications for the legal thinking of Muhammadiyah are to establish a foundation that is responsive and adaptable to essential legal ontological concepts. Such concepts must be reinforced by means of dissemination in law education at Muhammadiyah Higher Education Institutions (PTMA) in order to tackle contemporary challenges with relevant legal principles